Changes in behavior patterns or demographic structure? Re-estimating the impact of higher education on the average age of the first marriage - Lai, Ting; Huang, Yiheng; Xiong, Jinwu (Frontiers in Psychology, 2023)
During the last few decades, China implemented college enrollment expansion to accelerate the process of urbanization. However, most existing papers blaming that receiving higher education may delay people choosing to enter the age of first marriage, which in turn results in the age of the population. In this paper, we argued that the previous papers confused the total impact of higher education on the average age of the first marriage with the influence on individual’s behavior change, and thus led to overestimating the delayed effect of higher education on the age choosing behavior of first marriage. The present paper re-estimated the impact of higher education on the average age of the first marriage in China with both extensive and intensive margins using the duration model and qualified the pure effect on the behavior patterns change after removing macroeconomic factors. The results show that: (1) changes in either the demographic structure or behavior patterns due to higher education explain 63.41% or 36.59%, respectively, of the average marriage age delay; (2) the macro factors would delay the age of first marriage; (3) after controlling for demographic structure and macro factors, 3 years or more of higher education would only delay the choosing behavior of entering the first marriage by 0.84 years. Thus, we concluded that higher education does not completely squeeze the time of marriage, and the expansion of college enrollment could improve social and economic benefits.